Comparison of Simulated Low-Dose and Conventional-Dose CT for Preoperative Planning in Shoulder Arthroplasty. (1st June 2022) - Lorenzana, Daniel J.; Solomon, Justin; French, Robert J.; McCrum, Erin; Jonkergouw, Filip; Anakwenze, Oke A.; Lassiter, Tally; Samei, Ehsan; Klifto, Christopher S.
Abstract : Background: Shoulder computed tomography (CT) is commonly utilized in preoperative planning for total shoulder arthroplasty. Conventional-dose shoulder CT may expose patients to more ionizing radiation than is necessary to provide high-quality images for this procedure. The purpose of this study was to evaluate the utility of simulated low-dose CT images for preoperative planning using manual measurements and common preoperative planning software. Methods: Eighteen shoulder CT scans obtained for preoperative arthroplasty planning were used to generate CT images as if they had been acquired at reduced radiation dose (RD) levels of 75%, 50%, and 25% using a simulation technique that mimics decreased x-ray tube current. This technique was validated by quantitative comparison of simulated low-dose scans of a cadaver with actual low-dose scans. Glenoid version, glenoid inclination, and humeral head subluxation were measured using 2 commercially available software platforms and were also measured manually by 3 physicians. These measurements were then analyzed for agreement across RD levels for each patient. Tolerances of 5° of glenoid version, 5° of glenoid inclination, and 10% humeral head subluxation were used as equivalent for preoperative planning purposes. Results: At all RD levels evaluated, the preoperative planning software successfully segmented the CT images. Semiautomated software measurement of 25% RD images was within tolerances in 99.1% of measurements; for 50% RD images, within tolerances in 96.3% of measurements; and for 75% RD images, within tolerances in 100% of measurements. Manual measurements of 25% RD images were within these tolerances in 95.1% of measurements; for 50% RD images, in 98.8% of measurements; and for 75% RD images, in 99.4% of measurements. Conclusions: Simulated low-dose CT images were sufficient for reliable measurement of glenoid version, glenoid inclination, and humeral head subluxation by preoperative planning software as well as by physician-observers. These findings suggest the potential for substantial reduction in RD in preoperative shoulder CT scans without compromising surgical planning. Clinical Relevance: The adoption of low-dose techniques in preoperative shoulder CT may lower radiation exposure for patients undergoing shoulder arthroplasty, without compromising image quality.